Understanding Dengue Virus Capsid Protein Disordered N‑Terminus and pep14-23-Based Inhibition - Faustino, André F (2015)
Dengue virus (DENV) infection affects millions of people and is becoming a major global disease for which there is no specific available treatment. pep14-23 is a recently designed peptide, based on a conserved segment of DENV capsid (C) protein. It inhibits the interaction of DENV C with host intracellular lipid droplets (LDs), which is crucial for viral replication. Combining bioinformatics and biophysics, here, we analyzed pep14-23 structure and ability to bind different phospholipids, relating that information with the full-length DENV C. We show that pep14-23 acquires α-helical conformation upon binding to negatively charged phospholipid membranes, displaying an asymmetric charge distribution structural arrangement. Structure prediction for the N-terminal segment reveals four viable homodimer orientations that alternatively shield or expose the DENV C hydrophobic pocket. Taken together, these findings suggest a new biological role for the disordered N-terminal region, which may function as an autoinhibitory domain mediating DENV C interaction with its biological targets. The results fit with our current understanding of DENV C and pep14-23 structure and function, paving the way for similar approaches to understanding disordered proteins and improved peptidomimetics drug development strategies against DENV andsimilar Flavivirus infections.